IMPLEMENTATION OF THE PARIS AGREEMENT IN HANDLING CLIMATE CHANGE DUE TO FOREST FIRES IN INDONESIA 2015-2019 - Kinanthi Ahimsaning Gandhi; Roberto Octavianus Cornelis Seba; Suryo Sakti Hadiwijoyo (Jurnal Impresi Indonesia, 2024)
Forest fires in Indonesia have become an annual recurring event, considering that Indonesia is a member of the Paris Agreement and ratified the agreement. Thus, Indonesia must be able to commit to the contents of the contract. This research uses a qualitative method and will then be analyzed using the concepts that have been selected. The author uses secondary data with search techniques and data collection through written sources. It is understood that the Government has successfully developed various plans to reduce forest fires by the Paris Agreement commitments. However, there is hesitation in developing effective climate action, and shortcomings emerge, thus reinforcing that the lack of seriousness of this effort can affect Indonesia's Contribution to global efforts. The Government needs to be more serious in carrying out the commitments that have been made in a structured manner and hopes that it can resolve this case as well and as wisely as possible.